Holy places that have played a role in the urban evolution of damascus - Anabesh, Ghaleb (Universiti Kebangsaan Malaysia, 2014)
This study describes some of the shrines that contributed to the urban development of Damascus from the emergence of Islam to the middle ages. It also discusses the connection between the existence of holy places which attract pilgrims for religious and spiritual reasons, and the expansion of cities. The main sources for this study are writings in the ‘virtues of the Holy Land’ genre, augmented by the publications on this subject by Orientalists and Arab scholars.